Effects of Antimony and Tin Additions in the Intermediate Ir1-x-y SnxSbyO2+0.5y Layer of Mn–Mo–Sn–O Electrocatalyst for Hydrogen Production from Seawater Electrolysis - Bhattarai, Jagadeesh (Journal of Nepal Chemical Society, 2012)
The oxygen production anode for seawater electrolysis is composed of two layers on the titanium substrate. The outermost layer is electrocatalysts of ?-MnO2 type Mn1-x-yMoxSnyO2+x triple oxides and the intermediate layer preventing insulating oxide formation on the titanium substrate is generally IrO2. Due to limited amount of iridium, alternative materials to the intermediate IrO2 having sufficient durability and conductivity at high potentials for anodic polarization are required. In this context, decrease in the amount of IrO2 by substitution with SnO2 and increase in the electronic conductivity of the intermediate layer by Sb2O5 addition is performed in this works. The additions of SnO2 with Sb2O5 to the intermediate layer of the Mn-Mo-Sn-O/Ir1–x–ySnxSbyO2+0.5y/Ti anodes was effective to decrease the use of IrO2, maintaining the high electronic conductivity of the intermediate Ir1–x–ySnxSbyO2+0.5y layer and the high activity of oxygen evolution in seawater electrolysis at pH 1 for about 1550 h. The oxygen evolution efficiency of the nanocrystalline ?-MnO2 type Mn-Mo-Sn-O/Ir1–x–ySnxSbyO2+0.5y/Ti anodes with 0.208 M Ir4+, 0.208-0.416 M Sn4+ and 0.104 M Sb5+ in the intermediate layers was about 98.5 % during electrolysis for about 1550 hours without any degradation in 0.5 M NaCl solution of pH 1 at 25°C. DOI: http://dx.doi.org/10.3126/jncs.v27i1.6664 J. Nepal Chem. Soc., Vol. 27, 2011 78-85